Concomitant Drugs Prognostic Score in Patients With Metastatic Renal Cell Carcinoma Receiving Ipilimumab and Nivolumab in the Compassionate Use Program in Italy: Brief Communication. Issue 1 (4th January 2023) - Buti, Sebastiano; Basso, Umberto; Giannarelli, Diana; De Giorgi, Ugo; Maruzzo, Marco; Iacovelli, Roberto; Galli, Luca; Porta, Camillo; Carrozza, Francesco; Procopio, Giuseppe; Fonarini, Giuseppe; Lo Re, Giovanni; et al.
Abstract : A concomitant drug-based score was developed by our group and externally validated for prognostic and predictive purposes in patients with advanced cancer treated with immune checkpoint inhibitors (ICIs). The model considers the use of three classes of drugs within a month before initiating ICI, assigning score 1 for each between proton pump inhibitor and antibiotic administration until a month before immunotherapy initiation and score 2 in case of corticosteroid intake. In the present analysis, the drug score was validated in a prospective population of 305 patients with metastatic renal cell carcinoma treated with ipilimumab plus nivolumab in the first-line setting. The value of the model in predicting overall survival and progression-free survival was statistically significant and clinically meaningful, with an overall survival rate at 12 months of 73% vs. 44% ( P <0.0001), and median progression-free survival of 11.6 (95% CI: 9.1–14.1) months versus 4.8 (95% CI: 2.7–7.0) months ( P =0.002), respectively, for patients belonging to the favorable group (score 0–1) versus the unfavorable (score 2–4). Further development will be represented by the gut microbiome analysis according to the drug-based model classification and to the outcome of patients to ICI therapy to demonstrate the link between drug exposure and immune sensitivity.